2002
DOI: 10.1007/s10350-004-6368-9
|View full text |Cite
|
Sign up to set email alerts
|

Published Evidence Favors the Use of Suprapubic Catheters in Pelvic Colorectal Surgery

Abstract: The results reported favor suprapubic over urethral catheterization in that urinary tract infections are reduced, particularly in females, and the ability to attempt normal voiding is facilitated, particularly in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 24 publications
(35 reference statements)
0
17
0
2
Order By: Relevance
“…Endpoints considered in the studies were significant bacteriuria, clinical features of urine infection, failure to void normally after surgery, recatheterization and patient satisfaction. Two review articles 17,18 and one Cochrane Review meta-analysis 19 were found that described the use of the two catheter techniques in general, orthopaedic and gynaecological surgery. Randomized controlled trials were included in the meta-analysis if the study techniques and endpoints were suitably similar.…”
Section: Resultsmentioning
confidence: 99%
“…Endpoints considered in the studies were significant bacteriuria, clinical features of urine infection, failure to void normally after surgery, recatheterization and patient satisfaction. Two review articles 17,18 and one Cochrane Review meta-analysis 19 were found that described the use of the two catheter techniques in general, orthopaedic and gynaecological surgery. Randomized controlled trials were included in the meta-analysis if the study techniques and endpoints were suitably similar.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients with detrusor-sphincter dyssynergy require clean intermittent self-catheterisation, and others may need permanent catheterisation. In these cases suprapubic catheters offer a lower risk of infection and complications than intraurethral catheterisation [4,31].…”
Section: ■ Bladdermentioning
confidence: 99%
“…It is reported that in patients undergoing abdominal, gynecological or vascular surgery, postoperative discomfort was significantly higher in patients with urethral versus suprapubic catheterization. [5][6][7] Although many studies have recently shown that cystography can direct early catheter removal with no increase in morbidity, 8,9 and there has been a movement towards shortened catheterization, 10,11 the optimal timing for catheter removal is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%